2015
DOI: 10.18335/region.v2i1.63
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting jobs location choices by Discrete Choice Models: A sensitivity analysis to scale and implications for LUTI models

Abstract: Abstract. This paper proposes an empirical analysis of the sensitivity of Discrete Choice Model (DCM) to the size of the spatial units used as choice set. This is related to the well-documented Modifiable Areal Unit Problem). Employment location choices in Brussels, Belgium are used for the case study. DCMs are implemented within different Land Use and Transport Interactions (LUTI) models (UrbanSim, ILUTE) to forecast jobs and household location choices. Nevertheless, no studies have yet assessed their sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Let us now consider a lived research experience based on a participation to a EU project where researchers from several disciplines (including economists) aimed at applying the UrbanSim Land Use and Transport Interaction (LUTI) model to three European cities (Paris, Brussels and Zurich) (see Bierlaire et al, 2015). Jonathan Jones further developed this topic in his PhD dissertation and in the consequent scientific papers (see Jones et al 2015aJones et al and 2015bJones et al , 2017Thomas et al, 2018); these publications will be the main source of inspiration of this section and have the advantage of opening the debate to other disciplines than economics. We knew from the very beginning of the research project that LUTI models were data intensive and hence often leading to data crunching rather than modelling; as expected, we drowned into data problems among which the delineation of the cities and the choice of the basic spatial units.…”
Section: Butterflies Lions and Other Felinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us now consider a lived research experience based on a participation to a EU project where researchers from several disciplines (including economists) aimed at applying the UrbanSim Land Use and Transport Interaction (LUTI) model to three European cities (Paris, Brussels and Zurich) (see Bierlaire et al, 2015). Jonathan Jones further developed this topic in his PhD dissertation and in the consequent scientific papers (see Jones et al 2015aJones et al and 2015bJones et al , 2017Thomas et al, 2018); these publications will be the main source of inspiration of this section and have the advantage of opening the debate to other disciplines than economics. We knew from the very beginning of the research project that LUTI models were data intensive and hence often leading to data crunching rather than modelling; as expected, we drowned into data problems among which the delineation of the cities and the choice of the basic spatial units.…”
Section: Butterflies Lions and Other Felinesmentioning
confidence: 99%
“…Thomas et al 2018 The simulations reported confirm that the absence of control on city delineation strongly weakens the LUTI result, impacting in particular commuting times. The delineation of the city area plays a major role as well as the size of the spatial units (Jones, 2015b and2017) in transport modelling results and the consequences for not controlling these effects are clearly underestimated in the transport literature.…”
Section: Butterflies Lions and Other Felinesmentioning
confidence: 99%
“…The study area used in the SustainCity project (or "SustainCity Area") raises several concerns (see Thomas et al, 2015a;Jones et al, 2015a), since it encompasses municipalities having few relationships with the CBD and/or that belong to the catchment area of another city (Figure 1b). Previous works (Jones et al, 2015b;Thomas et al, 2015a) have demonstrated that the extent and composition of the study area may influence the parameter estimates of the location choice's sub models within UrbanSim and the outcomes from the model.…”
Section: Datamentioning
confidence: 99%
“…The variations of parameter estimates will, however, not be further discussed since we focus here on changes in the outputs of UrbanSim. We refer to Fotheringham and Wong (1991), Arauzo-Carod and Manjon-Antolin (2004), and Jones et al (2015b) for work dedicated to the MAUP.…”
Section: Econometric Sub Modelsmentioning
confidence: 99%
“…Two exceptions are worth mentioning. The first is Jones et al, which studies the effect of aggregation of alternatives on forecasting error for location choice models ( 17 ). In that study, the authors explicitly describe why variation in parameter estimates cannot reliably measure predictive performance in the forecasting phase.…”
Section: Introductionmentioning
confidence: 99%